The Ontology of Leadership in Crisis: Beyond the Directive Model Toward Collaborative-Adaptive Leadership - Imaduddin Fadhlurrahman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to examine whether leadership in crisis situations is ontologically distinct from leadership under normal conditions, and to demonstrate that collaborative-adaptive leadership constitutes the most ontologically honest response to the nature of crisis. This study employs philosophical library research through three complementary analytical approaches: philosophical inquiry, hermeneutical analysis, and critical comparative analysis. The directive model operates on three erroneous assumptions reality as already known, the sovereign singular subject, and time as linear sequence all of which collapse when crisis occurs. The phenomenology of Heidegger (Mitsein), Husserl (Einfühlung), and Arendt (plurality) demonstrates that crisis can only be responded to collectively, manifesting through three dimensions: collaboration as recognition of ontological complexity, empathy as ontological capacity, and trust as the foundation of a new shared world. Directive leadership is ontologically incompatible with the nature of crisis as a condition of human being-in-common (being-in-common). This study affirms the importance of integrating ontological, epistemological, and axiological dimensions in leadership theory, while simultaneously opening space for dialectical inquiry into phenomenologically-grounded leadership.